2021
DOI: 10.1016/j.jbc.2021.100547
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of an N6-methyladenosine-mediated positive feedback loop that promotes Epstein–Barr virus infection

Abstract: N6-methyladenosine (m 6 A) is among the most abundant mRNA modifications, particularly in eukaryotes, and is found in mammals, plants, and even some viruses. Although essential for the regulation of many biological processes, the exact role of m 6 A modification in virus–host interaction remains largely unknown. Here, using m 6 A -immunoprecipitation and sequencing, we find that Epstein–Barr virus (EBV) infection decreases the m 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…Since EBNA2, LP and 3 are expressed from a common C or W promoter driven transcript, we speculate that methionine metabolism also has important roles in EBNA post-transcriptional regulation, perhaps at the level of splicing. In support, methionine-derived SAM is the methyl donor for RNA methylation reactions, and RNA methylation is increasingly recognized as a key regulator of EBV-encoded mRNAs (Dai et al, 2021; Lang et al, 2019; Xia et al, 2021; Zheng et al, 2021). EBNA2 mRNAs are modified by N6-methyladenosine (m6A) marks, and knockdown of the m6A writer METTL3 decreases EBNA2 expression levels (Zheng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Since EBNA2, LP and 3 are expressed from a common C or W promoter driven transcript, we speculate that methionine metabolism also has important roles in EBNA post-transcriptional regulation, perhaps at the level of splicing. In support, methionine-derived SAM is the methyl donor for RNA methylation reactions, and RNA methylation is increasingly recognized as a key regulator of EBV-encoded mRNAs (Dai et al, 2021; Lang et al, 2019; Xia et al, 2021; Zheng et al, 2021). EBNA2 mRNAs are modified by N6-methyladenosine (m6A) marks, and knockdown of the m6A writer METTL3 decreases EBNA2 expression levels (Zheng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies reported that the EBV infection induces changes in N 6 -methyladenosine RNA methylation of viral and host cell mRNA. These epitransciptomic changes promoted EBV infection in vitro [ 391 , 392 ]. Once more, viruses take advantages of cellular processes to favor their life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In previous researches, m6A methylation negatively regulates the production of hepatitis C virus and avivirus Zika [11]. In other research, METTL3 inhibits Enterovirus 71 by autophagy regulation [12], decreases syndrome coronavirus clade 2 viral load and viral gene expression in host cells [13], and promotes Epstein-Barr virus infection of nasopharyngeal epithelial cells [14].…”
Section: Introductionmentioning
confidence: 96%